# Prove this wrong !

By register

@register (1065)

India

October 13, 2006 12:01pm CST

let a = b
a² = ab Multiply both sides by a
a² + a² - 2ab = ab + a² - 2ab Add (a² - 2ab) to both sides
2(a² - ab) = a² - ab Factor the left, and collect like terms on the right
2 = 1 Divide both sides by (a² - ab)

2 responses

@mnjtrana (14)

• India

22 Oct 06

u r wrong
because in step
2(a² - ab) = a² - ab
we know a=b
a² - ab=0
then anything multiplied by 0 is zero
u cannot cancel zero on both sides
so
2*0=1*0
i .e. 0=0
so simple

@RAMPersona (2036)

• Philippines

22 Oct 06

This cannot be, unless a² - ab is not equal to 0. If implementing division to prove an equation, it is imperative to specify that the divisor in this case a² - ab does not approach to 0 value or that lead to division by zero.